Experiências psicogeográficas em Caldas Novas-GO: identificando ambiências e personagens nas dinâmicas entre o turista e o morador - Mota, Matheus André Gomes (2021)
This investigation aims to analyze the experiences, urban ambiences and characters who practice the urban space of Caldas Novas through psychogeographic tools. The time frame of the analyzes and experiences comprises the years from 2019 to 2021, also covering the period of the COVID-19 pandemic which strongly impacted the city and its touristic economy, focusing on the daily life of the city, which results in totally different events and experiences, in a dialectic in which the tourist and resident Through the empirical and corporal analysis, it was possible to investigate the phenomena that involve the experience of the practitioners of this space, also investigating how the tourist dynamics have acted and impacted on the ambiences of the city and on the corporal experience. With the help of psychogeography and micropolitics such as cartography, critical analysis procedures that accompany the movement of reality, it was obtained a perception “inside out” of the urban space and the experiences of otherness that occur in it. The reiterative phenomena and events were gathered and analyzed with the help of the Grounded Theory and taxonomy, decoding them into larger concepts that were discussed after the experiments were carried out. At the end, the concepts of touristification, urban fantasy, reification of experience, dupliCity, dramatization of corporeal action and environmental emptying were decoded and obtained. In this way, the psychogeograhic procedures combined with cartographic analysis and taxonomy, allowed to verify several critical aspects in relation to the identification, experience and practice of the ambiences that involve the characters found, in addition to the ways in which the micropolitics of space act through the methodological inversion, as well as these can help in the apprehension, study and analysis of possible overlaps, disjunctions and socio-spatial conflicts inherent to the experience.